The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.engstruct.2015.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the flexural strength and serviceability of geopolymer concrete beams reinforced with glass-fibre-reinforced polymer (GFRP) bars

Abstract: Geopolymer concrete reinforced with glass-fibre-reinforced polymer (GFRP) bars can provide a construction system with high durability, high sustainability, and adequate strength. Few studies deal with the combined use of these materials, and this has been the key motivation of this undertaking. In this study, the flexural strength and serviceability performance of the geopolymer concrete beams reinforced with GFRP bars were evaluated under a four-point static bending test. The parameters investigated were nomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
53
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(56 citation statements)
references
References 28 publications
3
53
0
Order By: Relevance
“…3 findings were reported. The behaviour of GPC beams were investigated in several experimental studies [16][17][18][19][20][21][22] while other studies examined the structural performance of GPC columns [23][24][25][26]. In general, these studies showed the structural response of the GPC beams and columns was almost identical to that of OPC and thus concluded that the current design codes and models for OPC structures can be applied to calculate the strength of GPC beams and columns.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…3 findings were reported. The behaviour of GPC beams were investigated in several experimental studies [16][17][18][19][20][21][22] while other studies examined the structural performance of GPC columns [23][24][25][26]. In general, these studies showed the structural response of the GPC beams and columns was almost identical to that of OPC and thus concluded that the current design codes and models for OPC structures can be applied to calculate the strength of GPC beams and columns.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Maranan et al have investigated the flexural strength of glass fibre-reinforced polymer-reinforced geopolymer concrete (GFRP-RGPC) beams. e authors argued that the diameter of the bar had no significant effect on the beam's flexural performance, and the serviceability behaviour of a beam enhanced when the reinforcement ratio increases [19]. e GFRP-RGPC beams have structural properties that are suitable for civil infrastructure applications [20].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the researchers focused on replacing OPC by GPC in steel-reinforced concrete structures. ere is a limited study that combined the GPC with GFRP bars, by taking limited parameters [19], and the only study that uses CFRP bars in GPC beams has been undertaken by Ahmed et al [21], in which the investigated parameters were the reinforcement ratio and concrete type. A logical step, therefore, is to investigate the flexural behaviour of GPC beams reinforced with two common types of FRP bars (GFRP and CFRP) by achieving a precise comparison condition.…”
Section: Introductionmentioning
confidence: 99%
“…These authors showed that the geopolymer concrete beam strength results are viable for the use as structural elements, however they detected cracking in the curing stage and indicated that further analysis should be pursued. Maranan et al [22] investigated the structural performance of five GFRP-reinforced beams and compared their results to a steel-reinforced geopolymer concrete beam (the control specimen). As a result, they showed that the bending-moment capacities at concrete crushing failure of the GFRP-reinforced geopolymer concrete beams were 1.2-1.5 times greater than the one of the steel-reinforced geopolymer concrete beam with similar reinforcement ratio.…”
Section: Introductionmentioning
confidence: 99%